Speaker for the dead - Card, Orson Scott (London : Orbit Books, 2014)
Andrew Wiggin, itinerant speaker for the dead, is called to aid in the investigation of two deaths when a race of sapient beings is discovered on the planet Lusitania. Sequel to Ender's game.
Young Adult.
Young Adult
Keywords: Science fiction